Gene expression profiling reveals a role of immune system and inflammation in innate and stress-induced anxiety-like behavior - Gigliotta, Adrien; Trontti, Kalevi; Väänänen, Juho; Hovatta, Iiris (Frontiers in Genetics, 2023)
Anxiety is an evolutionarily conserved response that is essential for survival. Pathological anxiety, however, is a maladaptive response to nonthreatening situations and greatly affects quality of life. The recent COVID-19 pandemic has increased the prevalence of anxiety symptoms and highlighted the urge to identify the molecular events that initiate pathological anxiety. To this aim, we investigated the extent of similarity of brain region-specific gene expression patterns associated with innate and stress-induced anxiety-like behavior. We compared the cortico-frontal (FCx) and hippocampal (Hpc) gene expression patterns of five inbred mouse strains with high or low levels of innate anxiety-like behavior with gene expression patterns of mice subjected to chronic social defeat stress. We found significantly large overlap of the Hpc but small overlap of the FCx gene expression patterns in innate and stress-induced anxiety, that however, converged onto common inflammation and immune system canonical pathways. Comparing the gene expression data with drug-gene interaction datasets revealed drug candidates, including medrysone, simvastatin, captopril, and sulpiride, that produced gene expression changes opposite to those observed in innate or stress-induced anxiety-like behavior. Together, our data provide a comprehensive overview of FCx and Hpc gene expression differences between innate and stress-induced anxiety and support the role of inflammation and immune system in anxiety-like behavior.